Brazilian Consumer Capitalism and its History in Rio de Janeiro, São Paulo, and Beyond: Changing Consumption, the City, and the Country in the Twentieth Century - James Woodard (Iberoamericana. América Latina - España - Portugal)
Between the 1910s and the 1970s, the defining institutions, practices, and patterns of thought identified with something Brazilians call consumismo were installed in that country through processes focused on the cities of Rio de Janeiro and São Paulo. Business elites based in and acting upon the two cities were the key agents in these processes, which contributed greatly to the remaking of the two urban centers over the course of the twentieth century. By the 1970s, São Paulo was more closely identified with consumerism, but many residents of Rio de Janeiro were as beholden as any of their São Paulo counterparts with the new culture of consumption, to the profit of some and the consternation of others. Along the way, the two cities served as poles for the diffusion of that culture across the country’s varied regions.